2009
DOI: 10.1007/s10776-009-0104-2
|View full text |Cite
|
Sign up to set email alerts
|

Power Management and Data Rate Maximization in Wireless Energy Harvesting Sensors

Abstract: This paper considers the problem of power management and throughput maximization for energy neutral operation when using an energy harvesting sensor (EHS) to send data over a wireless link. The EHS is assumed to be able to harvest energy at a constant rate, and use a fixed part of the energy harvested in a slot for measuring the channel state. The rest of the energy harvested is available for transmission, however, it can be stored in an inefficient battery if it is not fully utilized. The key constraint that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Note, however, that the different diversity orders visibly manifest themselves only when > 10 dB. Also plotted for each < 0.25 curve is the analytical SER result, from (12), for asymptotically large with = 4 . We observe that the asymptotic results, despite their analytical simplicity, are good approximations even when is as small as four.…”
Section: A Symmetric Casementioning
confidence: 99%
“…Note, however, that the different diversity orders visibly manifest themselves only when > 10 dB. Also plotted for each < 0.25 curve is the analytical SER result, from (12), for asymptotically large with = 4 . We observe that the asymptotic results, despite their analytical simplicity, are good approximations even when is as small as four.…”
Section: A Symmetric Casementioning
confidence: 99%
“…In a theoretical framework [71], Murthy suggests that given time-slotted operation, energy neutral operation depends on four parameters: (i) the energy that is harvested in a slot, (ii) the maximum energy that is allowed for a single packet transmission by the hardware or power constraints (iii) the average data rate and (iv) the efficiency of battery storage. Thus perennial operation is assured by choosing the fourth parameter if the other three are already known or fixed.…”
Section: Rf Transceiversmentioning
confidence: 99%
“…Research on energy harvesting power management has recently gained lot of attention, especially in the field of WSNs [8,[18][19][20][21]. One of the earliest studies on energy harvesting power management can be found in reference [22].…”
Section: Power Management For Energy Harvesting Wsnmentioning
confidence: 99%